The Effect of Animated Video-Based Health Education on Mothers’ Knowledge and Attitudes Toward Stunting Prevention During the First 1000 Days of Life - Margaretha Angelia Prajogo; Irine Christiany; Endah Suprihatin; Mohammad Najib (International Journal of Advanced Health Science and Technology, 2026)
Stunting remains a major public health challenge, particularly in developing countries, because it negatively affects children’s physical growth, cognitive development, and future productivity. The first 1,000 days of life constitute a critical period for growth and development, during which nutritional deficiencies and inadequate maternal understanding of child health may increase the risk of stunting. Limited knowledge and unfavorable attitudes among mothers toward stunting prevention may hinder early preventive efforts. Therefore, effective educational interventions are needed to improve maternal awareness and promote positive health-related attitudes during this crucial period. This study aimed to determine the effect of animated video-based health education on mothers’ knowledge and attitudes regarding stunting prevention during the first 1,000 days of life. A quasi-experimental study with a pre-test–post-test control group design was conducted in the working area of the Sidotopo Wetan Health Center, Surabaya, Indonesia. A total of 44 respondents were selected using cluster sampling and divided into intervention and control groups. The independent variable was health education delivered through animated videos, while the dependent variables were mothers’ knowledge and attitudes toward stunting prevention. Data were collected using structured knowledge and attitude questionnaires. Statistical analysis was performed using the Wilcoxon Signed Rank Test to assess within-group differences and the Mann–Whitney U Test to compare differences between groups.  The findings revealed a statistically significant improvement in mothers’ knowledge and attitudes after receiving animated video-based health education on stunting prevention during the first 1,000 days of life (p < 0.05). Mothers in the intervention group demonstrated better post-test outcomes than those in the control group. In conclusion, animated video-based health education is effective in improving mothers’ knowledge and attitudes toward stunting prevention. This approach may serve as an engaging and practical educational strategy to strengthen maternal awareness and support early stunting prevention programs in community health settings.